(untitled) (Research, Society and Development, 2021)
The main focus of this article is the technological challenge as an applied element in the construction industry and especially in civil engineering. With this scenario in mind, the article analyzes the benefits, contributions and challenges of implementing this advanced technology and how it can and will improve the organizational standards of companies, as well as help improve company performance and the quality of the product offered to contractors. With the evolution of technological tools, today we can say that the implementation of BIM (Building Information Modeling) is present, which means an evolution of conventional processes (CAD), in the practices of design, production, management and delivery of architectural projects and works, but also a revolution, both in the market and in the education and practices of engineering and architecture. It is of paramount importance to train professionals with skills and abilities to work with this new platform and then be able to lead this process of change in the construction industry.